2007
DOI: 10.1074/jbc.m705358200
|View full text |Cite
|
Sign up to set email alerts
|

The Exchangeable Apolipoprotein ApoC-I Promotes Membrane Fusion of Hepatitis C Virus

Abstract: Cell entry of hepatitis C virus (HCV) is strikingly linked to lipoproteins and their receptors. Particularly, high density lipoprotein (HDL) enhances infectivity of HCV by involving the lipid-transfer function of the scavenger receptor BI, a receptor for both HDL and HCV. Here, we demonstrate that apoC-I, an exchangeable apolipoprotein that predominantly resides in HDL, specifically enhances HCVcc and HCVpp infectivity and increases the fusion rates between viral and target membranes via a direct interaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 101 publications
4
92
0
1
Order By: Relevance
“…Indeed, siRNA (small interfering RNA) directed to clathrin heavy chain and molecules that neutralise the acidic pH of endosomes produce a potent inhibition of the entry of HCVpp and HCVcc in various cell lines. ApoC-I, an exchangeable apolipoprotein that predominantly resides in HDL, was shown to increase HCV infectivity and the rate of fusion between viral and target membranes via a direct interaction with the virion surface (Dreux et al, 2007). Consistent with this, recent studies demonstrated that the C-terminal region of ApoC-1 associates with surface components of virions during morphogenesis (Meunier et al, 2008).…”
Section: Hcv Endocytosis and Genome Replicationsupporting
confidence: 57%
“…Indeed, siRNA (small interfering RNA) directed to clathrin heavy chain and molecules that neutralise the acidic pH of endosomes produce a potent inhibition of the entry of HCVpp and HCVcc in various cell lines. ApoC-I, an exchangeable apolipoprotein that predominantly resides in HDL, was shown to increase HCV infectivity and the rate of fusion between viral and target membranes via a direct interaction with the virion surface (Dreux et al, 2007). Consistent with this, recent studies demonstrated that the C-terminal region of ApoC-1 associates with surface components of virions during morphogenesis (Meunier et al, 2008).…”
Section: Hcv Endocytosis and Genome Replicationsupporting
confidence: 57%
“…However, it remains unclear if this system is truly indicative of HCV neutralization in vivo. Confounding factors such as enhancement of HCV infection by apolipoprotein (7,21) and epitope masking by high-density lipoprotein found in serum (37) are not present in this in vitro system. Unfortunately, the currently employed in vivo models have many drawbacks as well.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, apoB-containing lipoproteins (27) or high density lipoprotein (HDL) (28) appear to facilitate the interaction of HCV pseudoparticles or cell culture-grown HCV with scavenger receptor class B type I (SR-BI) (29). The exchangeable apolipoprotein apoCI, which is predominantly present in HDL, seems to interact with HCV particles via hypervariable region 1 (HVR1) in the N terminus of E2 thus promoting interaction and fusion of the HCV envelope with cellular membranes (30,31).…”
Section: Flagmentioning
confidence: 99%